Utility of Biology-Guided Radiotherapy to De Novo Metastases Diagnosed During Staging of High-Risk Biopsy-Proven Prostate Cancer - Gaudreault, Mathieu; Chang, David; Hardcastle, Nicholas; Jackson, Price; Kron, Tomas; Hanna, Gerard G.; Hofman, Michael S.; Siva, Shankar (Frontiers in Oncology, 2022)
Background: Biology-guided radiotherapy (BgRT) uses real time functional imaging to guide radiation therapy treatment. Positron emission tomography (PET) tracers targeting prostate specific membrane antigen (PSMA) are superior for prostate cancer detection than conventional imaging. This study aims to describe nodal and distant metastases distribution from prostate cancer and to determine the proportion of metastatic lesions suitable for BgRT. Methods: A single institution patient subset from the ProPSMA trial (ID ACTRN12617000005358) was analysed. Gross tumour volumes (GTV) were delineated on the CT component of a PSMA PET/CT scan. To determine the suitability of BgRT tracking zones, the normalized SUV (nSUV) was calculated as the ratio of SUVmax inside the GTV to SUVmean of adjacent three-dimensional shells of thickness 5 mm / 10 mm / 20 mm as a measure of signal to background contrast. Targets were suitable for BgRT if (1) nSUV was larger than an nSUV threshold and (2) non-tumour tissue inside adjacent shell was free of PET-avid uptake. Results: Of this cohort of 84 patients, 24 had at least one pelvic node or metastatic site disease, 1 to 13 lesions per patient, with a total of 98 lesions (60 pelvic nodes / 38 extra-pelvic nodal diseases and haematogenous metastases). Target volumes ranged from 0.08 cm3 to 9.6 cm3 while SUVmax ranged from 2.1 to 55.0. nSUV ranged from 1.9 to 15.7 / 2.4 to 25.7 / 2.5 to 34.5 for 5 mm / 10 mm / 20 mm shell expansion. Furthermore, 74% / 68% / 34% of the lesions had nSUV ≥ 3 and were free of PSMA PET uptake inside GTV outer shell margin expansion of 5 mm / 10 mm / 20 mm. Adjacent avid organs were another lesion, bladder, bowel, ureter, prostate, and liver. Conclusions: The majority of PSMA PET/CT defined radiotherapy targets would be suitable for BgRT by using a 10 mm tracking zone in prostate cancer. A subset of lesions had adjacent non-tumour uptake, mainly due to the proximity of ureter or bladder, and may require exclusion from emission tracking during BgRT.